Sambandet i tallungskog mellan skötselmetod och älgbetesskador - Tunell, Christian (2019)
Moose cause major problems in our young pine forest stands. This study is trying to investigate the casual reactions of damages to stands and to individual trees caused by moose. The study is based on data from 16 objects in Vemhåns Moose Management Area.